Advantages of the seedling method of cultivation in medicinal plant production - Semenko, M.; Pospielov, S. (Scientific Progress & Innovations, 2023)
The cultivation of medicinal and essential oil crops is of great interest to producers of various forms of ownership. Important problems are the deficiency of seeds and the chemical polymorphism of the raw materials. Industrial cultivation requires the availability of high-quality seeds on the market and well-established seed production, but often producers combine different batches or use non-varietal seeds with low sowing qualities. This can greatly complicate the growing process and have a negative impact on the quality and stability of yields and product quality. The purpose of the article is to analyze the agrotechnical, phytocoenotic, phytochemical advantages of introducing seedling technologies in medicinal plant production, taking into account the experience of other plant growing industries. This approach allows controlling plant growth processes from the very beginning, ensuring their maximum quality and stability. The article provides a detailed analysis and systematization of information on the use of seedling technology in various areas of agriculture. An important element is the use of modern growth regulators and microfertilizers, which allows to increase the quality of seedlings, their rooting and survival. This approach also simplifies the mechanization of seeding and planting processes, reducing costs for these operations and increasing accuracy. In addition, it allows to prepare the area for planting as well as reduce the fight against weeds thanks to a longer interval between planting seedlings. Equally important is the possibility of using seedlings both for generatively propagated and vegetatively propagated plants. This method of cultivation ensures the unity of raw materials, providing a stable biochemical composition of crops. As a result, the widespread implementation of the seedling method can be the optimal solution to the problem of the lack of seeds, will simplify the process of planting and caring for young plants, and will allow obtaining raw materials with a stable biochemical composition. This is an important step in ensuring the stability and quality of medicinal and essential oil crops in agriculture